Coordination of multiple regulation pathways contributes to the tolerance of a wild citrus species (Citrus ichangensis '2586') against Huanglongbing. (January 2020) - Wu, Haodi; Hu, Yan; Fu, Shimin; Zhou, Changyong; Wang, Xuefeng
Abstract: Huanglongbing (HLB), a highly destructive disease of citrus production worldwide, is presumably caused by ' Candidatus Liberibacter asiaticus' ( C Las) because Koch's postulates have not been fulfilled. No HLB resistant genotypes have been so far identified in commercial citrus species, hindering the development of resistance breeding. China is an important center of citrus germplasm resources with abundant wild citrus species. However, studies on the susceptibility or resistance of these wild citrus and their response mechanisms to C Las infection have been limited. In this study, we evaluated the symptom development and transcriptional differences among two wild citrus species, Citrus ichangensis '2586' and C. daoxianensis, and the highly susceptible C. sinensis . No typical symptoms was observed and much less C Las accumulated in C. ichangensis, compared with C. daoxianensis and C. sinensis . Much greater number of differentially expressed genes were identified and pathways were perturbed in diseased C. sinensis, followed by diseased C. daoxianensis then C. sinensis . Many pathways including cell wall, secondary metabolism, stress responses, RNA transcriptional regulation and protein modification were differentially regulated in three diseased citrus species but with different preferences. Particularly, genes associated with carbohydrate metabolism, callose deposition and photosynthesis process were significantly regulated in C Las-infected C. daoxianensis and C. sinensis but not in C Las-infected C. ichangensis . Taken together, it seem to indicate that the relatively successful defenses of C. ichangensis against multiplication of C Las and its symptom development may involve a novel mechanism in which the carbohydrate metabolism and photosynthesis process was balanced with the normal physiology of the plant, and coordinated with other regulation pathways. Evaluation of wild citrus resources to C Las infection is promising for citrus HLB resistance breeding in the future. Highlights: " Candidatus Liberibacter asiaticus" reproduced faster in Citrus sinensis than in C. ichangensis and C. daoxianensis . pp2 genes related with callose deposition, starch synthesis and photosynthesis were not regulated in affected C. ichangensis. A group of genes in secondary metabolism were significantly up-regulated in C. ichangensis.